Streamlining operations: transitioning maintenance checklists functionality to a paperless system at Pusat Sains Negara - Hamni@Farid, Norynn Farisya; Ismail, Azianti (2024)
This paper describes a case study undertaken at Pusat Sains Negara and it aims to explore the application of the digital transformation strategy to enhance the operational performance. The study concentrated on the utilisation of digital tools and methodologies to simplify the operations and enhance the communication process in the organisation. This study incorporated methodologies which include PDCA Cycle, 5 Whys Analysis, 5S Concept as well as Fishbone Diagram in order to pinpoint problems in operations and provide effective solutions for them. Digital tools provide a modern organisation with an agile and responsive operational framework that can satisfy the contemporary market demands. By following a proper methodology, data from exhibition departments and operation units of Pusat Sains Negara provide insights into the efficiency of digital transformation initiatives. In the beginning of the study, it was seen that making use of digital means and methods can greatly benefit productivity. This is because time taken is reduced to 75%, coordination increases among teams and savings are made in terms of costs by 94.18%. Overall, this paper contributes to existing knowledge about digital transformation by showing its effectiveness on organisational operational performance improvement. Specifically, findings from this study offer Pusat Sains Negara some tips for getting started with digital transformation among other similar establishments.